An e-readiness assessment model for disaster management. (2016) - Benssam, Ali; Nouali-Taboudjemat, Nadia; Nouali, Omar
One of the most important factors for an effective use of information and communication technologies (ICT) in different fields is the e-readiness of the environment in which evolve such technologies. Bringing technological solutions before assessing the maturity of such environment was, in the most cases, behind the registered failures of the related projects. In this paper, we propose an assessment model to evaluate countries' e-readiness in the field of disaster management. To elaborate and validate the proposed model, we used two main techniques: Delphi and the analytical hierarchy process, from statistic and decision-making domains, respectively. The proposed model includes five dimensions and 34 indicators representing the principal elements that influence the effective use of ICT in disaster management. This model can be used by countries, mainly from the developing world, to assess their readiness to successfully use ICT and to suggest areas for improvement, in the field of disaster management.